Short-Term Magnesium Deficiency Triggers Nutrient Retranslocation in Arabidopsis thaliana - Ogura, Takaaki; Kobayashi, Natsuko I.; Hermans, Christian; Ichihashi, Yasunori; Shibata, Arisa; Shirasu, Ken; Aoki, Naohiro; Sugita, Ryohei; Ogawa, Takahiro; Suzuki, Hisashi; Iwata, Ren; Nakanishi, Tomoko M.; et al. (Frontiers in Plant Science, 2020)
Magnesium (Mg) is essential for many biological processes in plant cells and its deficiency causes yield reduction in crop systems. Low Mg status reportedly affects photosynthesis, sucrose partitioning and biomass allocation. However, earlier physiological responses to Mg deficiency are scarcely described. Here, we report that Mg deficiency in Arabidopsis thaliana first modified the mineral profile in mature leaves within one or two days, then affected sucrose partitioning after four days and net photosynthesis and biomass production after six days. The short-term Mg deficiency reduced the contents of phosphorus (P), potassium, manganese, zinc and molybdenum in mature but not in expanding (young) leaves. While P content decreased in mature leaves, P transport from roots to mature leaves was not affected, indicating that Mg deficiency triggered retranslocation of the mineral nutrients from mature leaves. A global transcriptome analysis revealed that Mg deficiency triggered the expression of genes involved in defence response in young leaves.